Congenital External Carotid‐Internal Carotid Artery Anastomosis Diagnosed by MR Angiography. Issue 1 (23rd June 2011) - Uchino, Akira; Saito, Naoko; Watadani, Takeyuki
ABSTRACT: We present what we believe is the first report of external carotid‐internal carotid artery anastomosis, which forms a large arterial ring at the proximal cervical internal carotid artery (ICA). If the small channel of the proximal cervical ICA is occluded, the remaining large channel of the external carotid artery may be diagnosed as a nonbifurcating cervical carotid artery .